Ibrutinib suppresses intracellular mycobacterium tuberculosis growth by inducing macrophage autophagy. Issue 6 (June 2020) - Hu, Yunlong; Wen, Zhihua; Liu, Song; Cai, Yi; Guo, Jiubiao; Xu, Yuzhong; Lin, Dachuan; Zhu, Jialou; Li, Dechang; Chen, Xinchun
Highlights: Ibrutinib reduces intracellular Mtb survival in human macrophages. Ibrutinib induces complete autophagy flux targeting intracellular Mtb . Ibrutinib induces autophagy through inhibition of BTK/Akt/mTOR pathway. Ibrutinib reduces Mtb load in mediastinal node and spleen of Mtb infected mice. Ibrutinib is a potential host-directed therapy candidate against TB. Summary: Tuberculosis (TB) is a major cause of morbidity and mortality worldwide. The host-directed therapy is a promising strategy for TB treatment that synergize with anti-TB treatment drugs. In this study, we found that the anti-chronic lymphocytic leukemia drug, ibrutinib, inhibited the growth of intracellular Mtb in human macrophages. Mechanisms studies showed that ibrutinib treatment significantly decreased p62 and increased LC3b proteins in Mtb infected macrophages. In addition, ibrutinib increased LC3b colocalization with intracellular Mtb and auto-lysosome fusion. Furthermore, inhibition of autophagy by using siRNA targeting ATG7 abolished the effect of ibrutinib-mediated suppression of intracellular Mtb . Next, we found that ibrutinib induced autophagy was through inhibition of BTK/Akt/mTOR pathway. Finally, we confirmed that ibrutinib treatment significantly reduced Mtb load in mediastinal node and spleen of Mtb infected mice. In conclusion, our data suggest that ibrutinib is a potential host-directed therapy candidate against TB.